Development Development of the One in Diversity Application for Class V Students on Indonesian Diversity Material: Pengembangan Aplikasi Satu Dalam Keberagaman Untuk Siswa Kelas V Pada Materi Keberagaman Indonesia - Widiyanti, Isti; Hanifah, Nurdinah; Nugraha, Rana Gustian (Pedagogia : Jurnal Pendidikan, 2024)
This study employs Research and Development (RnD) methodology, utilizing the ADDIE model, to develop the One In Diversity application aimed at enhancing grade V students' learning of Indonesian Diversity in PPKn. The application's development involved analysis, design, development, implementation, and evaluation stages. Media and material experts evaluated the application, achieving scores of 82.5% and 95.3% respectively, indicating high quality. Large and small group trials further validated its effectiveness, with scores of 86.29% and 87.47% respectively. This innovative approach offers promising implications for educators seeking to integrate technology into their teaching methods, fostering enhanced student engagement and comprehension in diverse subject matter. Highlights: Innovative Learning Solution: "One In Diversity" app enhances PPKn learning Systematic Development: ADDIE model ensures effective app creation. Expert Validation: High scores from assessments and trials validate app's efficacy. Keywords: Application Development, PPKn, Indonesian Diversity